Complexation of molecular clips containing fragments of diphenylglycoluril and benzocrown ethers with paraquat and its derivatives - Kikot', Leonid S.; Kulygina, Catherine Yu.; Lyapunov, Alexander Yu.; Shishkina, Svetlana V.; Zubatyuk, Roman I.; Bogaschenko, Tatiana Yu.; Kirichenko, Tatiana I. (Beilstein Journal of Organic Chemistry, 2017)
The complexation of molecular clips containing fragments of diphenylglycoluril and benzocrown ethers with paraquat and its derivatives has been studied both in solution and in the solid state. In this paper we studied the influence of the crown ether ring size and the nature of the substituents at the nitrogen atoms of the paraquat derivatives on the composition and stability of these complexes.
Keywords: complexation; crown ethers; "host–guest chemistry"; molecular clips; paraquat

(untitled) - Pedersen, C. J. (J. Am. Chem. Soc., 1967)

(untitled) - Allwood, B. L.; Shahriarizavareh, H.; Stoddart, J. F.; Williams, D. J. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Ashton, P. R.; Campbell, P. J.; Glink, P. T.; Philp, D.; Spencer, N.; Stoddart, J. F.; Chrystal, E. J. T.; Menzer, S.; Willams, D. J.; Tasker, P. A. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Bruns, C. J.; Stoddart, J. F. (Acc. Chem. Res., 2014)

(untitled) - Stoddart, J. F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Fahrenbach, A. C.; Bruns, C. J.; Cao, D.; Stoddart, J. F. (Acc. Chem. Res., 2012)

(untitled) - Niess, F.; Duplan, V.; Sauvage, J.-P. (Chem. Lett., 2014)

(untitled) - Faiz, J. A.; Heitz, V.; Sauvage, J.-P. (Chem. Soc. Rev., 2009)

(untitled) - Logtenberg, H.; Areephong, J.; Bauer, J.; Meetsma, A.; Feringa, B. L.; Browne, W. R. (ChemPhysChem, 2016)

(untitled) - Vlatković, M.; Feringa, B. L.; Wezenberg, S. J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Bryant, W. S.; Jones, J. W.; Mason, P. E.; Guzei, I.; Rheingold, A. L.; Fronczek, F. R.; Nagvekar, D. S.; Gibson, H. W. (Org. Lett., 1999)

(untitled) - Zhang, M.; Zhu, K.; Huang, F. (Chem. Commun., 2010)

(untitled) - Hsueh, S.-Y.; Lai, C.-C.; Liu, Y.-H.; Peng, S.-M.; Chiu, S.-H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Ballardini, R.; Balzani, V.; Credi, A.; Gandolfi, M. T.; Venturi, M. (Acc. Chem. Res., 2001)

(untitled) - Loeb, S. J. (Chem. Soc. Rev., 2007)

(untitled) - Rowan, A. E.; Elemans, J. A. A. W.; Nolte, R. J. M. (Acc. Chem. Res., 1999)

(untitled) - Hardouin-Lerouge, M.; Hudhomme, P.; Sallé, M. (Chem. Soc. Rev., 2011)

(untitled) - Schenning, A. P. H. J.; de Bruin, B.; Rowan, A. E.; Kooijman, H.; Spek, A. L.; Nolte, R. J. M. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Han, Y.; Meng, Z.; Ma, Y.-X.; Chen, C.-F. (Acc. Chem. Res., 2014)

(untitled) - Han, T.; Chen, C.-F. (Org. Lett., 2006)

(untitled) - Ma, Y.-X.; Han, Y.; Cao, J.; Chen, C.-F. (Org. Biomol. Chem., 2013)

(untitled) - Chen, C.-F. (Chem. Commun., 2011)

(untitled) - Jiang, Y.; Cao, J.; Zhao, J.-M.; Xiang, J.-F.; Chen, C.-F. (J. Org. Chem., 2010)

(untitled) - Peng, X.-X.; Lu, H.-Y.; Han, T.; Chen, C.-F. (Org. Lett., 2007)

(untitled) - Cao, J.; Lu, H.-Y.; You, X.-J.; Zheng, Q.-Y.; Chen, C.-F. (Org. Lett., 2009)

(untitled) - Cui, J.-F.; Chen, C.; Gao, X.; Cai, Z.-W.; Han, J.-W.; Wong, H. N. C. (Helv. Chim. Acta, 2012)

(untitled) - Bogaschenko, T. Y.; Lyapunov, A. Y.; Kikot’, L. S.; Mazepa, A. V.; Botoshansky, M. M.; Fonari, M. S.; Kirichenko, T. I. (Tetrahedron, 2012)

(untitled) - Kikot’, L. S.; Lyapunov, A. Y.; Kulygina, C. Y.; Bogaschenko, T. Y.; Zubatyuk, R. I.; Shishkin, O. V.; Kirichenko, T. I. (J. Inclusion Phenom. Macrocyclic Chem., 2014)

(untitled) - Lyapunov, A.; Kirichenko, T.; Kulygina, C.; Zubatyuk, R.; Fonari, M.; Kyrychenko, A.; Doroshenko, A. (J. Inclusion Phenom. Macrocyclic Chem., 2015)

(untitled) - Lyapunov, A. Y.; Lobach, A. V.; Yakovenko, I. S.; Kulygina, E. Y.; Shishkina, S. V.; Zubatyuk, R. I.; Kirichenko, T. I. (Macroheterocycles, 2015)

(untitled) - Vincenti, M. (J. Mass Spectrom., 1995)

(untitled) - Schalley, C. A. (Int. J. Mass Spectrom., 2000)

(untitled) - Mahan, E. J.; Dennis, J. A. (Org. Lett., 2006)

(untitled) - Asakawa, M.; Ashton, P. R.; Dehaen, W.; L'abbé, G.; Menzer, S.; Nouwen, J.; Raymo, F. M.; Stoddart, J. F.; Tolley, M. S.; Toppet, S.; White, A. J. P.; Williams, D. J. (Chem. – Eur. J., 1997)

(untitled) - Vetrogon, V. I.; Lukyanenko, N. G.; Schwing-Weill, M.-J.; Arnaud-Neu, F. (Talanta, 1994)

(untitled) - Zhang, J.; Huang, F.; Li, N.; Wang, H.; Gibson, H. W.; Gantzel, P.; Rheingold, A. L. (J. Org. Chem., 2007)

(untitled) - Ashton, P. R.; Philp, D.; Reddington, M. V.; Slawin, A. M. Z.; Spencer, N.; Stoddart, J. F.; Williams, D. J. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Ashton, P. R.; Ballardini, R.; Balzani, V.; Bělohradský, M.; Gandolfi, M. T.; Philp, D.; Prodi, L.; Raymo, F. M.; Reddington, M. V.; Spencer, N.; Stoddart, J. F.; Venturi, M.; et al. (J. Am. Chem. Soc., 1996)

(untitled) - Elemans, J. A. A. W.; Claase, M. B.; Aarts, P. P. M.; Rowan, A. E.; Schenning, A. P. H. J.; Nolte, R. J. M. (J. Org. Chem., 1999)

(untitled) - Wang, H.-X.; Hu, S.-Z.; Meng, Z.; Han, Y.; Chen, C.-F. (Chem. – Asian J., 2016)

(untitled) - Řeźač, J.; Hobza, P. (Chem. Rev., 2016)